SELF-LOVE AND SELF-ACCEPTANCE: REDEFINING IDEAL BEAUTY THROUGH ITS REPRESENTATION IN SCARS TO YOUR BEAUTIFUL - Ida Rosida; Dinni Yulia Saputri (LITERA, 2019)
The ideal beauty has a significant impact on social life. Those who feel their body doesn’t meet the idealize body view, some might have body dissatisfaction and lower body appreciation. This study aims to explore a broader definition and understanding of the beauty as it is represented in Scars to Your Beautiful, a song by Alessia Cara, both its lyric and music video. Using content analysis and supported by the concept of the figure of Speech, cinematography, and representation by Stuart Hall completed the investigation on this beauty ideal. The result shows that Scars to Your Beautiful strive to redefine the term of beauty which cannot be determined only by certain criteria such as having a thin body, white skin, flawless and addressed to women only, but beauty reaches a broader definition in all shapes, sizes, colors, even the gender. These findings highlight the importance of self-love and self-acceptance in the social context. Keywords: beauty ideals, representation of beauty, body dissatisfaction